Chronic Kidney Disease in Female Domestic Short Hair Cat - Umaiyah, Ifara; Noviatri, Aldila; Kristanto, Dwi; Prasetyo, Dodik; Rickyawan, Nofan (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2024)
Chronic kidney disease (CKD) is a decrease or loss of the kidney's ability to excrete unused products, concentrate urine and convert electrolytes. A female Domestic short hair cat with clinical findings of Polyuria/polydipsia, decreased muscle mass, anorexia, dehydration, hypersalivation. Defecation was found a solid, dry, black-brownish yellow consistency (Score 2) and urine was dark yellow. The physical examination revealed a drastic decrease in body temperature and tachycardia. Hematological examination showed leukocytosis and hypochromic macrocytic anaemia. The result of blood smear tests showed the presence of neutrophils and other lymphocytes in large numbers. Blood chemistry analysis showed an increase BUN and creatinine (Azotemia) and also increase SGOT. Urinalysis examination revealed proteinuria, ketonuria, urobilinogenuria and hypersthenuria. Fecal examination revealed positive helminthiasis in the form of Toxocara cati eggs which was confirmed by the finding of adult worms in the duodenum during necropsy. The therapy given to the case cat included 50 ml/kgBW Ringer's lactate, 0,5 ml/kgBW Amoxicillin-Clavulanate, 2 mg/kgBW Ranitidine, 0,2 mg/kgBW Ipakitin® and 0,5 ml/kgBW Imboost®. A week after therapy, the cat's condition deteriorated further, with an undetectable temperature, seizures, critical condition and not being able to survive, so a necropsy was carried out. Macroscopic results of the kidneys during the necropsy procedure showed that the korteks of kidneys were pale with no change in size. The histophatology finding in the kidneys are necrosis and fibrosis tubulointerstitial. Microscopy finding in duodenum is inflammation and adult worm Toxocara cati in the lumen duodenum. The conclusion is this cat with diagnose Chronic kidney disease with histophatologycal finding is glomerulonephritis and duodenitis.